2009
DOI: 10.1200/jco.2008.19.4860
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized Trial of Two Different Modalities of Flushing Central Venous Catheters in Pediatric Patients With Cancer

Abstract: An increased complication rate was found with normal saline flushing, but additional investigation is warranted to clarify whether it is related to saline use or to once-a-week flushing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 31 publications
2
76
1
Order By: Relevance
“…We contacted three individual study authors for further study details and were able to find further information for two studies (Goossens et al, 2013, Smith et al, 1991. Of the 10 studies, three met the inclusion criteria (Cesaro et al, 2009, Goossens et al, 2013, Smith et al, 1991 and were included in this review. Details of data extraction are summarised in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We contacted three individual study authors for further study details and were able to find further information for two studies (Goossens et al, 2013, Smith et al, 1991. Of the 10 studies, three met the inclusion criteria (Cesaro et al, 2009, Goossens et al, 2013, Smith et al, 1991 and were included in this review. Details of data extraction are summarised in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…A flow chart detailing the identification of studies can be found in Figure 1. The studies undertaken by Cesaro et al, (2009) and Goossens et al, (2013) were of medium duration (25 and 23 months respectively) and included follow-up periods of 14 and six months respectively. The Smith et al, (1991) study was a cross-over study of two, three-and-a-half month time periods (total duration seven months) and did not include a follow-up period.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 However, a prospective study that evaluated twice weekly heparin flushes versus weekly saline flushes in 203 children with Broviac-Hickman CVCs demonstrated an increased rate of catheter occlusions (83% vs. 41%, P=0.0002) and catheter infections (65% vs. 44%, P=0.01) with saline flushes. 53 Although most guidelines for subcutaneous ports recommend monthly flushes when not in use, two studies have demonstrated that increased periods of time between flushes, from six weeks to three months, may not increase the frequency of complications. 54,55 Additional prospective trials are required to accurately determine the frequency and type of solution required to optimize CVC function and minimize complications.…”
Section: Prophylaxismentioning
confidence: 99%
“…The dose of heparin varies in function of catheter type and period of closing. 16 Guidelines for the prevention of complications associated with CVC vary greatly. The widest recommendation is for the use of heparin to prevent occlusion, but some articles suggest that 0.9% sodium chloride (normal saline) may be as effective.…”
Section: Discussionmentioning
confidence: 99%